2007
DOI: 10.1073/pnas.0611572104
|View full text |Cite
|
Sign up to set email alerts
|

Single-site mutations in the carboxyltransferase domain of plastid acetyl-CoA carboxylase confer resistance to grass-specific herbicides

Abstract: Grass weed populations resistant to aryloxyphenoxypropionate (APP) and cyclohexanedione herbicides that inhibit acetyl-CoA carboxylase (ACCase; EC 6.4.1.2) represent a major problem for sustainable agriculture. We investigated the molecular basis of resistance to ACCase-inhibiting herbicides for nine wild oat (Avena sterilis ssp. ludoviciana Durieu) populations from the northern grain-growing region of Australia. Five amino acid substitutions in plastid ACCase were correlated with herbicide resistance: Ile-1,7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
176
1
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(196 citation statements)
references
References 20 publications
(52 reference statements)
13
176
1
5
Order By: Relevance
“…These high values for the RF factors are strong evidence of a target site mechanism of resistance in the E. indica biotype from Mato Grosso, Brazil. Further molecular studies have indicated an Asp-2078-Gly substitution in the R population endowed resistance to both APP and CHD herbicides (Figure 1). The same mutation has been reported in other grass weeds (Délye et al, 2005;Liu et al, 2007;Yu et al, 2007;Hochberg et al, 2009) and endows resistance of these to ACCase-inhibitors.…”
Section: Molecular Studiesmentioning
confidence: 75%
See 1 more Smart Citation
“…These high values for the RF factors are strong evidence of a target site mechanism of resistance in the E. indica biotype from Mato Grosso, Brazil. Further molecular studies have indicated an Asp-2078-Gly substitution in the R population endowed resistance to both APP and CHD herbicides (Figure 1). The same mutation has been reported in other grass weeds (Délye et al, 2005;Liu et al, 2007;Yu et al, 2007;Hochberg et al, 2009) and endows resistance of these to ACCase-inhibitors.…”
Section: Molecular Studiesmentioning
confidence: 75%
“…Cross-resistance is referred as resistance to several herbicides that affect one target enzyme, and usually is endowed by a single gene (Délye, 2005). Herbicide crossresistance on many plant species have been documented due to ACCase enzymes with amino acid substitutions at the positions: 1781 (White et al., 2005), 1999 (Liu et al, 2007); 2027 (Délye et al, 2003;Liu et al, 2007;Gherekhloo et al, 2012); 2041 (Délye et al, 2003;Zhang & Powles, 2006;Liu et al, 2007); 2078 (Délye et al, 2005;Kaundun, 2010;Hochberg et al, 2009); at 2088 (Yu et al, 2007), and 2096 (Délye et al, 2005). The choice of herbicide to control a resistant population is complicated by the fact that the specific amino acid substitutions in one enzyme may give different patterns of cross resistance to the different herbicides that affect it (Powles &Yu, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The cytosolic enzyme (ACC2) makes malonyl-CoA for very long-chain fatty acids, flavonoids, and signaling compounds. The plastid form of the enzyme in wheat and other grasses is sensitive to three classes of highly effective herbicides: aryloxyphenoxypropionates, cyclohexanediones, and pinoxaden (2)(3)(4)(5). We have shown that the parasite Toxoplasma gondii has two ACCs as well, one located in the apicoplast, where it is involved in de novo fatty acid synthesis for lipids and the lipoic acid cofactor of pyruvate dehydrogenase.…”
Section: Fatty Acid Metabolism | Human Healthmentioning
confidence: 99%
“…1 In studies with resistant A. myosuroides and L. rigidum populations from France, neither heterozygous nor homozygous mutants of 1781-Leu were found to be resistant to clethodim, haloxyfop, or clodinafop, and the genotype 1781-Leu/2041-Asn was not found to be resistant to clethodim in a seed germination assay (Délye et al, 2002b(Délye et al, , 2005. Conversely, in a recent study in Avena sterilis, 2027-Cys and 2041-Asn mutations were found to be associated with resistance to the CHD herbicides tralkoxydim and sethoxydim, respectively (Liu et al, 2007). Similarly, the 2041-Asn mutation in Phalaris paradoxa was found to confer resistance to most CHD herbicides with a lower level resistance to clethodim (Hochberg et al, 2007).…”
Section: Combination Of Mutant 1781/2027 or 1781/2041 Alleles Endowinmentioning
confidence: 99%
“…The Asp-2078-Gly mutation confers resistance to many APP and CHD herbicides including clethodim. The Trp-1999-Cys mutation confers resistance only to the APP herbicide fenoxaprop (Liu et al, 2007).…”
mentioning
confidence: 99%